Pelatihan Pembuatan Pupuk Organik Cair(POC) Pada kelompok Pembudidaya Ikan Bandeng di Kabupaten Pangkep - Asni Anwar; Murni Murni; Sri Andayaningsih; Nurinzani Hasyim; Andi Almi; Aksan Aksan; Apriliani Malik (To Maega : Jurnal Pengabdian Masyarakat, 2023)
The community of milkfish cultivators who are members of the "Sipakatau" milkfish cultivator group in Pangkep Regency, until now still has various kinds of obstacles to increase its production. The problem is related to the use of chemical fertilizers before the stocking of milkfish seeds, the aim is to fertilize the growth of klekap and other phytoplankton to be used as natural food for young milkfish, so that it has an impact on the growth of green and blue algae that produce geosmin as the cause of the smell of mud and fishy in fish. milkfish. One alternative that is done to address this problem is to apply the use of liquid organic fertilizer (LOF). The method of implementing the activities is carried out using the methods of coordination, discussion, counseling, training and assistance to partners. Based on the results of community service activities carried out in the Sipakatau group, it can be concluded that so far this group of cultivators has used chemical fertilizers to increase the fertility of their pond soil. Through this training activity, the partner group became aware of and skilled in making and applying the use of liquid organic fertilizer (LOF) based on fermented duck manure to produce organic milkfish in Pangkep Regency. The advice given in this activity is that further assistance should be carried out regarding the use of LOF and applications in ponds so that environmental sustainability can be maintained through the use of organic fertilizers.Â Key Word:Â Milkfish, Natural feed, Pangkep, Liquid Organik Fertilizer